Bioethics and human rights in international law: genetic engineering, euthanasia and/or physician assisted suicide - de Oliveira, Carina Teresa (Department of Public Law, 2023)
Medical advancements and improved scientific knowledge has introduced various benefits to society, while also creating contentious debates and issues concerning the impacts these medical advancements and/or procedures have had on human rights. In particular, the impact on human rights that medical and scientific advancements have arisen in regards to specific forms of genetic engineering, euthanasia and physician-assisted suicide. This dissertation is aimed at specifically focusing on the dichotomy of ideologies and legislation concerning the rights to human dignity and privacy in relation to the medical advancements involving genetic engineering, euthanasia and physician-assisted suicide. Genetic engineering is broadly considered to be an umbrella term that comprises various medical technologies, including preimplantation and prenatal genetic testing and selection, as well as genetic editing. Preimplantation and prenatal genetic testing enables the detection of a disease or defective condition of an embryo or foetus, while genetic editing enables the alteration of an embryo or foetuses genes to remove mutations or defective conditions to improve the overall living condition of the embryo when it is born. These different practices within the broad realm of genetic engineering use medical technologies to essentially “pick and choose” what physical and medical traits an individual should bear, in an attempt to avoid offspring with serious illnesses or unwanted conditions that could potentially cause the individual a lifetime of suffering. Although it is important to note that genetic engineering has also confronted a plethora of ethical and legal objections, a specific form of medical technology within the broad framework of genetic engineering, specifically preimplantation and prenatal genetic testing, is still generally more accepted on a global scale, both by society and by legislatures, than the practices of genetic editing or euthanasia and/or physician-assisted suicide, which aims to restore an individual's human dignity, privacy and autonomy by assisting these individuals suffering from severe illnesses or defective conditions to peacefully conclude their undignified lives. Euthanasia and/or physician assisted suicide, essentially involves an individual or medical practitioner administering a lethal agent to a patient in order to relieve them of their severe and chronic suffering. This dissertation intends to analyse the bioethics and international law concerning the dichotomy present between the application of preimplantation and prenatal genetic testing utilized in the selection process of a life to attempt to ensure an individual without illnesses, with the more dominant prohibition on euthanasia and/or physician assisted suicide to terminate the life of a human being suffering with those very same traits, conditions and/or illnesses that preimplantation and prenatal genetic testing intends to detect and then allow an individual to either terminate the embryo or foetus, or not. This bioethical debate seems to be increasingly contradictory, whereby preimplantation and prenatal genetic testing, although still facing criticism by some states, is being introduced and accepted far more commonly across the globe, while the option of an individual having the freedom of autonomy to make an informed decision to bring an end to their suffering through euthanasia and/or physician assisted suicide, is largely rejected. This dissertation essentially explores the irony present in bioethics in the manner in which there exists far greater societal and legislative support for preimplantation and prenatal genetic testing and selection to effectively allow the avoidance of chronic suffering, than there is for the protection of the human dignity and autonomy of individuals by terminating the severe chronic suffering caused by these very same conditions that the former medical interventions intend to eradicate.